Celebrity endorsements in non-profit settings: a literature review / Sharifah Nurafizah Syed Annuar and Stephen Laison Sondoh Jr - Syed Annuar, Sharifah Nurafizah; Stephen Laison Sondoh Jr (Universiti Teknologi MARA Sabah, Kota Kinabalu, 2016)
This paper provides the review of several studies on celebrity endorsements in non-profit settings. Topics discussed in this review include a brief introduction of celebrity endorsements, previous studies on celebrity endorsement in non-profit settings and the attributions of celebrity endorsers in enhancing the effectiveness of messages as mentioned in the literature. This paper presents the results of a systematic literature review to locate articles and examine the contents. A total of 15 articles were reviewed for this paper. Hence, several propositions are developed based on the discussions of the literature. Conclusions and implications are presented at the end of the paper.